2017
DOI: 10.1182/bloodadvances.2017006148
|View full text |Cite
|
Sign up to set email alerts
|

Agonistic targeting of TLR1/TLR2 induces p38 MAPK-dependent apoptosis and NFκB-dependent differentiation of AML cells

Abstract: Key Points• TLR1 is upregulated on primitive AML cells.• Agonistic targeting of TLR1/TLR2 induces apoptosis and differentiation of primitive AML cells in vivo.Acute myeloid leukemia (AML) is associated with poor survival, and there is a strong need to identify disease vulnerabilities that might reveal new treatment opportunities.Here, we found that Toll-like receptor 1 (TLR1) and TLR2 are upregulated on primary MLL-AF9 AML cells, we demonstrate that p53 is dispensable for Pam3CSK4-induced apoptosis and differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 62 publications
0
36
0
1
Order By: Relevance
“…Subsequent gene ontology analyses indicated that the genes regulated by E2F4 were enriched for the regulation of the MAPK signalling pathway ( Figure 6B). 20,21 To determine the specific mechanism of E2F4-induced tumour cell proliferation and differentiation, we further examined the protein levels of MAPK, p-MAPK, ERK and p-ERK when E2F4 expression levels were manipulated in AML cells. 18,19 The MAPK signalling pathway is also studied in AML.…”
Section: Overexpression Of Ezh2 Reverses E2f4mediated Inhibition Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent gene ontology analyses indicated that the genes regulated by E2F4 were enriched for the regulation of the MAPK signalling pathway ( Figure 6B). 20,21 To determine the specific mechanism of E2F4-induced tumour cell proliferation and differentiation, we further examined the protein levels of MAPK, p-MAPK, ERK and p-ERK when E2F4 expression levels were manipulated in AML cells. 18,19 The MAPK signalling pathway is also studied in AML.…”
Section: Overexpression Of Ezh2 Reverses E2f4mediated Inhibition Ofmentioning
confidence: 99%
“…18,19 The MAPK signalling pathway is also studied in AML. 20,21 To determine the specific mechanism of E2F4-induced tumour cell proliferation and differentiation, we further examined the protein levels of MAPK, p-MAPK, ERK and p-ERK when E2F4 expression levels were manipulated in AML cells. Knockdown of E2F4 by shRNA significantly decreased the protein levels of p-MAPK and p-ERK compared with those in NB4 and THP-1 cells transduced with NC-shRNA ( Figure 6C).…”
Section: Overexpression Of Ezh2 Reverses E2f4mediated Inhibition Ofmentioning
confidence: 99%
“…They recommend the study of conjugated SLPs in phase I and II safety and immunogenicity of clinical trial . Pam3CSK4, a TLR1 / TLR2 agonist, induces apoptosis in a mouse model of acute myeloid leukemia . In addition, Pam3 CysSK4‐containing compound elicits antitumor activity in in vivo model of mammary cancer .…”
Section: Tlr2mentioning
confidence: 99%
“…В случае ТПР3 адаптером служит TRIF (внутриклеточный адаптерный белок, содержащий TIR-домен, включающий интерферон β), связанный с синтезом интерферона (ИФН) 1-го типа. ТПР-регулируемым сигнальным путям активации генов цитокинов и ИФН посвящено множество публикаций [7][8][9][10][11][12][13][14][15][16][17]. Механизмы, связывающие иммунные реакции и воспаление с развитием опухоли, изучены недостаточно.…”
Section: Introductionunclassified